Correlation of sintered microstructure with green density in thick film PZT - Mortara, L.; Navarro, A.; Whatmore, Roger W.; Alcock, Jeffrey R. (Trans Tech Publications, 2003)
High density and low grain size are essential for the production of thick-film ceramics, in order that they possess adequate strength for any subsequent processing steps. In this paper sintered density and grain size were studied as function of green density and firing temperature. Wafers possessing a higher green density showed a more homogeneous microstructure and a higher sintered density.